Determination of the selenium contents of waste rocks of iron ore mining in the Pilbara, Western Australia using ICP-MS - Rajabian Tabesh, Donya (Curtin University, 2014)
International reference materials were employed to investigate the efficacy of ICP-MS for determination of selenium in rocks. Results indicate that significant inaccuracies may occur in the reported Se content of rocks, particularly those containing high Fe and Al, using routine procedures employed by commercial laboratories in trace element analysis. Analysis of waste rocks from three Pilbara iron ore mines revealed significant potential sources of selenium contamination with lignite and carbonaceous shales particularly enriched in selenium.